2018
DOI: 10.1021/jacs.8b02547
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Ni–Al Bimetallic Catalyzedexo-Selective C–H Cyclization of Imidazoles with Alkenes

Abstract: A Ni-Al bimetallic catalyzed enantioselective C-H exo-selective cyclization of imidazoles with alkenes has been developed. A series of bi- or polycyclic imidazoles with β-stereocenter were obtained in up to 98% yield and >99% ee. The bifunctional SPO ligand-promoted bimetallic catalysis proved to be critical to this challenging stereocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 87 publications
1
71
0
3
Order By: Relevance
“…Recently, a method for enantioselective C−H cyclization of imidazole with alkene catalyzed by secondary phosphine oxide ligands was developed. The method was extended on benzimidazoles, and imidazopyridines …”
Section: Figurementioning
confidence: 99%
“…Recently, a method for enantioselective C−H cyclization of imidazole with alkene catalyzed by secondary phosphine oxide ligands was developed. The method was extended on benzimidazoles, and imidazopyridines …”
Section: Figurementioning
confidence: 99%
“…In this system, Al III would perform a dual role: that of a Lewis acid activator as in the reaction reported by Hiyama and co‐workers, and that of an anchoring site for the SPO ligand. Following this hypothesis, we investigated our previously reported Taddol‐derived SPO ( L 1 ) for the reaction . Without or with AlMe 3 , traditional phosphines and carbenes did not produce any of the desired product 3 a , except for some side products from decarbonylation and hydrocarbomoylation .…”
Section: Methodsmentioning
confidence: 99%
“…[31] In contrast, Ye et al reported on the nickel-catalyzed asymmetric exo-selective hydroarylation of alkenes with tethered imidazole derivatives (Scheme 7). [32] Here,t he TADDOL-based HASPO preligand 23 promoted nickel-aluminum bimetallic catalysis. Such TADDOL-SPOs had previously been employed in asymmetric organocatalysis, [33] but their use in enantioselective transitionmetal catalysis had remained limited.…”
Section: Càha Ctivation Of (Hetero)arenes 321 Intramolecular Reactmentioning
confidence: 97%